Pulmonary langerhans cell histiocytosis secondary to Marijuana use: a case report and systematic review of the literature - Ibrahim Zahid; Aruba Sohail; Roohan Tahir; Matthew Belardo; Brandon Hooks (BMC Pulmonary Medicine)
Abstract Background Pulmonary Langerhans Cell Histiocytosis (PLCH) is a rare interstitial lung disease primarily affecting young to middle-aged smokers. While traditionally linked to tobacco use, there is growing evidence that cannabis use may contribute to PLCH. Methods We present a case of a 52-year-old male with PLCH associated with heavy cannabis use. Diagnostic evaluations included CT scan of the chest and histopathological examination of a lung biopsy. In addition, a comprehensive review of the literature was conducted to identify and analyze similar cases of PLCH linked to cannabis use. Databases searched included PubMed and Google Scholar, following PRISMA guidelines. Results The patient presented with dyspnea, cough and unintentional weight loss. The patient had a 20-year history of smoking approximately ten cannabis blunts per day. Despite normal initial chest X-ray findings, a CT scan of his chest revealed upper lobe predominant cystic changes and emphysema. Histopathology from a transbronchial biopsy confirmed the presence of Langerhans cells, consistent with PLCH. Literature review identified five additional case reports of PLCH associated with cannabis use, involving patients aged 16 to 59 years, with a mean age of 35.8 years. Common clinical presentations included cough, dyspnea, and chest pain, with radiographic findings of nodules and cysts. Treatment was primarily targeted towards smoking cessation, which led to clinical improvement in all cases. Conclusions This case underscores the potential association between heavy cannabis use and the development of PLCH. With the increasing prevalence of cannabis consumption, it is essential to recognize cannabis as a possible risk factor for PLCH. Further research is needed to understand the pathophysiological mechanisms underlying cannabis-related PLCH. As cannabis use becomes more prevalent with changing legislation, understanding its impact on lung health and potential role in diseases like PLCH is increasingly important.